[Ru(bpy)2(7-CH3-dppz)]2+ and [Ru(phen)2(7-CH3-dppz)]2+ as metallointercalators that affect third-strand stabilization of the poly(U)˙poly(A)*poly(U) triplex. Issue 5 (21st March 2016) - Tang, Wuzhi; Zhu, Zhiyuan; Tan, Lifeng
Abstract : Ru1 and Ru2 not only can stabilize the triplex, but also can serve as molecular "light switches" for the triplex. In addition, the two complexes stabilizing third-strand is weaker, reflecting the binding of Ru1 and Ru2 with the triplex is favored by the Watson–Crick base-paired duplex. Abstract : Stable RNA triplexes play key roles in many biological processes. However, due to Hoogsteen base pairing, triplexes are thermodynamically less stable than the corresponding duplexes. To understand the factors effecting the stabilization of RNA triplexes by octahedral ruthenium(ii ) complexes, two Ru(ii ) complexes, [Ru(bpy)2 (7-CH3 -dppz)] 2+ (Ru1 ) and [Ru(phen)2 (7-CH3 -dppz)] 2+ (Ru2 ), have been synthesized and characterized in this work. The interactions of the two Ru(ii ) complexes with the poly(U)˙poly(A)*poly(U) triplex are investigated by spectrophotometry, spectrofluorometry, circular dichroism as well as viscometry. The results demonstrate that the two complexes are able to enhance the stability of the RNA triplex and serve as molecular "light switches" for the triplex. However, Ru1 and Ru2 affecting the stabilization of the third strand are significantly weaker than that of the Watson–Crick base-paired duplex, suggesting that the binding of the two complexes with the triplex is favored by the Watson–Crick base-paired duplex to a large extent. In addition, considering the nature of Ru1 and Ru2, we presume that their binding differences may be due to different ancillary ligand effects. This study further advances our knowledge on the interaction of RNA triple-stranded structures with metal complexes, particularly with Ru(ii ) complexes.